Grooming behaviour of honey bees (Hymenoptera: Apidae) on varroa (Mesostigmata: Varroidae) - ARANEDA-D., XIMENA; BERNALES-M., MANUEL; SOLANO-S., JAIME; MANSILLA-V., KARINA (Revista Colombiana de Entomología, 2010)
Among the factors that can help to diminish and control populations of Varroa destructor in colonies of Apis mellifera is grooming behaviour. This behaviour consists of the capacity of the bee to detect, bite and eliminate parasites in the phoretic stage. In this investigation we evaluated the presence of grooming behavior in bee colonies through observations of damaged mites. For this we used six colonies of A. mellifera in Langstroth type beehives, which were evaluated daily for 30 days in April and May of 2008. The samples consisted of daily mite fall onto metal sheets coated with vaseline, placed in the floor of each beehive for a period of 24 hours. The results showed 95% of fallen mites dead and 5% alive out of a total of 2005 mites. We found 49% of mites with damage and 51% without damage. Based on these observations, it may be possible to choose colonies with significant grooming behavior such as dorsal damage and complete damage, which can be very useful to study bee selection and to design strategies of integrated management of the mite V. destructor.